Improving of Mathematics Understanding Through Interactive Powerpoint Media of Third Grade Students - Diah Retno Wati (Universitas Sebelas Maret, 2020)
The purpose of this study was to improve students' understanding of mathematics learning in grade III SD. This research is a Classroom Action Research which is conducted in 3 cycles. Each cycle consists of stages of planning, implementing, observing and reflecting. The subjects of this study were students of class III SDN Tegowanuh in the academic year 2020/2021, totaling 30 students. Data collection techniques using observation and tests. Data analysis includes data reduction, data presentation, and drawing conclusions. Research shows that the use of interactive powerpoint media can improve understanding of the third grade students' time conversion in the 2020/2021 academic year as evidenced by the percentage of completeness of learning outcomes and the class average. In the first cycle it was 50% with a class average of 80.3 to 100% with a class average of 89.8 in the second cycle and 100% with a class average of 94 in the third cycle.